Quality Quality of Work Life, Motivation, and Employee Performance on PT. Bank BCA Branch Jember (International Journal of Scientific Research and Management (IJSRM), 2018)
This study aims to determine and to analyze the direct effect of quality of work life on the work motivation, the effect of work motivation on employee performance, the effect of quality of work life on the employee performance, and the indirect effect of quality of work life on the employee performance through work motivation. The sample were 162 employees obtained by census sampling technique. The data used was primary data generated from distribution of questionnaires. Hypotheses were tested using path analysis. The results found that there is a significant direct and positive influence of quality of work life on work motivation, there is a significant direct and positive influence of work motivation on performance, there is a significant and positive influence on the quality of work life on performance, there is a positive and significant indirect effect of quality of work life on the employee performance but the effect is not as strong as the direct effect.This study has both theoretical and practical implications. These findings are able to reinforce previous studies on the study of quality of work life, motivation, and employee performance. In addition, this research gives input to the management of PT. Bank BCA to maintain quality of work life aspects and motivation in the business to improve the employee performance.